Hands-On Clay-Based Learning: Enhancing Higher-Order Thinking Skills in Preschool Children - Ani Supratini; Rina Hizriyani; Cucu Sopiah (Atfaluna: Journal of Islamic Early Childhood Education, 2026)
Purpose – This study aimed to address the prevalence of teacher-centered instruction in preschools, which limits children's opportunities for active exploration and higher-order thinking skills (HOTS). It investigated whether hands-on clay-based learning activities could systematically enhance preschool children’s ability to analyze, evaluate, and create through meaningful manipulative experiences. Design/methods/approach – This study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, comprising planning, action, observation, and reflection, conducted over two research cycles. The participants were 20 children aged 5–6 years in Group B at PAUD Bunga Bangsa, Cirebon Regency, Indonesia. Data were gathered through classroom observations, performance assessments, and documentation, using validated instruments that measured three HOTS dimensions: analyzing (C4), evaluating (C5), and creating (C6). Data were analyzed using qualitative descriptive analysis and percentage analysis. Findings – The intervention produced substantial improvements in children's HOTS. The proportion of children achieving the expected developmental level increased from 30% during the pre-cycle to 60% in Cycle I, and reached 85% in Cycle II. Significant progress was also observed across individual dimensions, with analyzing skills increasing from 35% to 90%, evaluating skills from 25% to 80%, and creating skills from 30% to 85%. These exact figures confirm that clay-based learning effectively promotes cognitive engagement. Research implications/limitations – The primary limitation of this study is its implementation in a single preschool setting with a small sample size of 20 participants. Furthermore, the Classroom Action Research design was conducted without a control or comparison group, which limits the statistical generalizability of the findings and prevents drawing definitive causal conclusions. Practical implications – The findings suggest that early childhood educators can seamlessly integrate low-cost, clay-based manipulative learning into daily classroom practices. This approach establishes a more dynamic, engaging, and child-centered environment that fosters early problem-solving, reflection, and creative thinking. Originality/value – This study provides objective empirical evidence on how accessible, low-cost manipulative materials can be systematically aligned with advanced cognitive dimensions (C4–C6) in early childhood education. It bridges the gap between hands-on play and rigorous HOTS development, offering a baseline for future experimental research with larger, diverse samples.